Impact of eradication therapy of Helicobacter pylori in children with chronic immune thrombocytopenic purpura - Mahmoud M. Hodeib; Ahmed G. Ali; Nsreen M. Kamel; Shaimaa A. Senosy; Ehab M. Fahmy; Ahmed Abdelsadik; Mohamed H. Maebed (SpringerOpen, 2021)
Abstract Background Although some investigators have confirmed the association between H. pylori and chronic ITP in adults, studies in pediatric patients are still few and have produced conflicting results. The study was carried out to detect the prevalence of H. pylori among chronic ITP children and to investigate the impact of treatment of H. pylori infection on platelet count response. Results The prevalence of H. pylori in chronic ITP children was 63%. The platelet count was statistically significantly higher among H. pylori stool antigen (HpSA)-negative children. A significant difference was reported in which platelet count increased from 70.55 ± 4.788 million/μL before H. pylori eradication therapy to 110.78 ± 15.128 million/μL after therapy. Conclusion We concluded that H. pylori eradication therapy was effective in increasing platelet count in H. pylori-positive chronic ITP patients.